Intraoperative magnetic resonance imaging in epilepsy surgery: systematic review of the literature and meta-analysis - Tomschik, Matthias; Shawarba, Julia; Mercea, Petra A.; Dorfer, Christian; Rössler, Karl (Journal of Neurosurgical Sciences, 2022)
INTRODUCTION: Intraoperative magnetic resonance imaging (iopMRI) is increasingly incorporated into neurosurgery to improve outcomes. However, its usefulness in epilepsy surgery remains debated. To elucidate its current role, we conducted a systematic review of the data published to date. EVIDENCE ACQUISITION: We performed a systematic review of the available literature using the PubMed, Scopus, and Embase database. Only articles detailing the usefulness of iopMRI in quantifiable measures were included. Different aspects of iopMRI in epilepsy surgery were analyzed and two meta-analyses summarizing its impact on extent of resection and seizure outcomes performed. EVIDENCE SYNTHESIS: A total of 33 articles met the inclusion criteria, comprising a total of 1313 patients, both children and adults operated under iopMRI guidance. The mean rate of return to surgery was 29.2% in 30 articles reporting this number. Eleven publications were eligible for meta-analysis of seizure outcome in patients with refractory epilepsy, who had undergone surgery with iopMRI (N.=294) compared to controls (N.=298). Eight articles described the impact of iopMRI on the radiological extent of resection. In both regards, usage of iopMRI improved outcomes in our meta-analysis with an OR of 3.8 and 4.75, respectively. CONCLUSIONS: This work presents the first meta-analysis of the value of iopMRI in epilepsy surgery. Its use resulted in an improvement of the desired extent of resection and led to a better seizure outcome compared to conventional surgery. Understanding its benefits might help improve surgical strategies in traditional, open epilepsy surgery.
CRIS-Team Scopus Importer:2022-12-02

Microsurgical treatment of cranial and spinal dural arteriovenous fistulas for acute occlusion: a single institution's experience - Winter, F.; Böhm, Lea; Shawarba, Julia; Callegari, K.; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2022)
Objectives: To determine the success rate of primary microsurgical treatment of both cranial and spinal dural arteriovenous fistulas (cdAVFs and sdAVFs).
CRIS-Team WoS Importer:2022-08-26

Prediction of Hearing Preservation in Vestibular Schwannoma Surgery According to Tumor Size and Anatomic Extension - Bozhkov, Yavor; Shawarba, Julia; Feulner, Julian; Winter, Fabian; Rampp, Stefan; Hoppe, Ulrich; Dörfler, Arnd; Iro, Heinrich; Buchfelder, Michael; Rössler, Karl (Otolaryngology-Head and Neck Surgery, 2021)
Objective: Vestibular schwannoma (VS) surgery is feasible for various tumor sizes that are inappropriate for wait and scan or radiosurgery. The predictive value of 2 grading systems was investigated for postoperative hearing preservation (HP) in a large series. Study Design: Retrospective analysis. Setting: Neurosurgical patient database of the University of Erlangen was queried between 2014 and 2017. Methods: Retrospective single-center analysis on 138 VSs operated on via a retrosigmoidal approach. The mean tumor size was 20.4 mm (SD, 7.6 mm) with fundal infiltration in 67.4%. The overall resection rate was 93.5%. Tumors were classified preoperatively by the 3-tier Erlangen grading system depending on size or the anatomically based 4-tier Koos grading system. Results: Preoperative hearing preservation was found in 70.3% of patients and was significantly correlated to tumor size (P =.001). For Erlangen grading, a mean postoperative serviceable hearing preservation rate of 32% was achieved: 83.3% for tumors <12 mm, 30.3% for tumors between 12 and 25 mm, and 5.3% for tumors >25 mm. In contrast, according to Koos grading, postoperative serviceable hearing preservation was 100% for grade 1 tumors (meatal), 35.6% for grade 2 (cisternal), 23.1% for grade 3 (brainstem contact), and 21.7% for grade 4 (brainstem compression). Of the total cohort, 86% had normal or nearly normal postoperative facial function (House-Brackmann grades 1 and 2). Conclusion: Surgery on small VSs can achieve excellent hearing preservation. Different grading has a significant influence on and correlates with postoperative hearing preservation. Tumor size seems more important than anatomic relationship.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Erlangen vestibula schwannoma grading; grading systems; hearing preservation; Koos vestibular schwannoma grading; vestibular schwannoma surgery